Dispersed radiance : caste, gender and modern science in India - Sur, Abha (New Delhi : Navayana, 2022)
"How did caste, nationalism and gender affect modern science? Dispersed Radiance offers a social history of Physics in India in the first half of the twentieth century. Abha Sur writes about the life and work of two preeminent physicists$1 (BC.V. Raman and Meghnad Saha. In their caste, political investment and cultural upbringing, Raman and Saha were diametric opposites. Raman hailed from a conservative Tamil brahmin family, and Saha from an unlettered rural family of a shudra caste in eastern Bengal. How did their social locations impact the kind of science they pursued? Sur also reconstructs a collective history of Raman$1 (Bs women students$1 (BLalitha Chandrasekhar, Sunanda Bai and Anna Mani$1 (Beach a scientist who did not her due. Author: Abha Sur is a scientist turned historian of science. She is presently a lecturer in the Program in Women's and Gender Studies and a research associate in the Program in Science, Technology, and Society at MIT."--s
Keywords: India -- Caste -- Social classes; India -- Caste -- Social conditions